Left-Dislocation in Latin Topics and Syntax in Republican Texts - Halla-aho, Hilla (Amsterdam Studies in Classical Philology, 2018)
Based on a detailed analysis of syntax, information structure and pragmatic organization, Left-dislocation in Latin by Hilla Halla-Aho examines how left-dislocation is used in republican Latin comedy, prose and inscriptions as a device to introduce topics. Readership: Scholars working on Latin syntax, especially in the republican period, and generally those interested in how syntax, particularly in its non-standard form, is influenced by information structure and pragmatic organization.